Multi-agent systems : 12th European Conference, EUMAS 2014, Prague, Czech Republic, December 18-19, 2014, Revised selected papers /: 12th European Conference, EUMAS 2014, Prague, Czech Republic, December 18-19, 2014, Revised selected papers. (2015) - Unknown
No abstract available